Shaping Civil Liability in the Digital Age: AILD and the Revisited PLD - Rimkutė, Deimantė (Teisė, 2024)
This article assesses two proposals for directives put forward by the European Commission: The Artificial Intelligence Liability Directive and the revised Product Liability Directive. The first part of the article introduces and compares the two proposals for directives. The subsequent part assesses the key elements of the Directives, including the scope of the application; the proposed changes to procedural law (disclosure of evidence, presumptions); and the rules of the revised Product Liability Directive on the identification of product defects. The article concludes with suggested improvements to the proposals for both Directives.
Keywords: non-contractual liability; strict liability; product liability; artificial intelligence